Sensitive detection of Treponema pallidum by using the polymerase chain reaction. - Burstain, J M (1991)
We have developed a sensitive assay for Treponema pallidum subsp. pallidum (T. pallidum), the agent of veneral syphilis, based upon the polymerase chain reaction (PCR). A 658-bp portion of the gene encoding the 47-kDa membrane immunogen was amplified, and the PCR products were probed by DNA-DNA hybridization with a 496-bp fragment internal to the amplitifed DNA. The assay detected approximately 0.01 pg of purified T. pallidum DNA, and positive results were obtained routinely from suspensions of treponemes calculated to contain 10 or more organism and from some suspensions calculated to contain a single organism. Specific PCR products were obtained for the closely related agent of yaws, Treponema pallidum subsp. pertenue, but not with human DNA or DNAs from other spirochetes (including Borrelia burgdoferi), skin microorganisms, sexually transmitted disease pathogens, and central nervous system pathogens. T. pallidum DNA was detected in serum, cerebrospinal fluids, and amniotic fluids from syphilis patients but not in in nonsyphilitic controls. T. pallidum DNA was also amplified from paraffin-embedded tissue. The diagnosis of syphillis by using PCR may become a significant addition to the diagnostic armamentarium and a valuable technique for the investigation of syphilis pathogenesis.